Examining creativity in teacher training: Perspectives from music education - McMillan, Jan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
As we enter the „Age of Intelligence‟ (Buzon, 2011) the focus of Malaysia and other developing nations has turned to the value of human capital and its ability to produce creative, independent leaders as a primary investment for future growth. Creativity is nothing new to music educators: music has continually been a creative learning and teaching tool; employing methods and approaches that have been transferred from parent to child, sage to novice and teacher to student and which develops aural, visual, physical, kinaesthetic and written communication skills. Music education can provide teaching and learning examples to develop these previously underestimated soft skills which are now in high demand. Notwithstanding, both Australia and Malaysia have identified music education in schools (Classroom and instrumental) as an area in dire need of improvement and programs of curricula improvements have begun. Gwatkin (2008) identified the need for consistency of government policy, teacher training within disciplines and an increase in creative approaches. Outcomes of a large scale national and international empirical study discerned that both classroom and instrumental (piano) teachers valued the input of creative programs and would like more training in this area. Results of a trial program that focused on creative philosophies for prospective classroom teachers at undergraduate level demonstrated that students were inspired and would have liked more in their overall course of study. More recent applications of creative philosophies for Malaysian music undergraduates have also been rewarding. Recommendations of the study included design templates for future courses for music educators to include creative practices with global implications for all teachers and the institutions that serve them. Together with new government paradigm for education that underlines the necessity for creativity, these results demonstrate such approaches are warranted and are applicable to all disciplines.